De novo designed transmembrane peptides activating the α5β1 integrin. Issue 5 (10th July 2018) - Mravic, Marco; Hu, Hailin; Lu, Zhenwei; Bennett, Joel S; Sanders, Charles R; Orr, A Wayne; DeGrado, William F
Abstract: Computationally designed transmembrane α-helical peptides (CHAMP) have been used to compete for helix–helix interactions within the membrane, enabling the ability to probe the activation of the integrins αIIb β3 and αv β3 . Here, this method is extended towards the design of CHAMP peptides that inhibit the association of the α5 β1 transmembrane (TM) domains, targeting the Ala–X3 –Gly motif within α5 . Our previous design algorithm was performed alongside a new workflow implemented within the widely used Rosetta molecular modeling suite. Peptides from each computational approach activated integrin α5 β1 but not αV β3 in human endothelial cells. Two CHAMP peptides were shown to directly associate with an α5 TM domain peptide in detergent micelles to a similar degree as a β1 TM peptide does. By solution-state nuclear magnetic resonance, one of these CHAMP peptides was shown to bind primarily the integrin β1 TM domain, which itself has a Gly–X3 –Gly motif. The second peptide associated modestly with both α5 and β1 constructs, with slight preference for α5 . Although the design goal was not fully realized, this work characterizes novel CHAMP peptides activating α5 β1 that can serve as useful reagents for probing integrin biology.